Testing Protein Stress Signals in Peripheral Immunocytes Under the Same Treatment Capable of Decreasing the Incidence of Alzheimer’s Disease in Bladder Cancer Patients - Benjamin Y. Klein; Ofer N. Gofrit; Charles L. Greenblatt (Current Issues in Molecular Biology)
Several studies showed that the incidence of Alzheimer’s disease (AD) is significantly lower in patients with non-muscle invasive bladder cancer (NMIBC) treated with intravesical bacillus Calmette–Guérin (BCG) instillations compared to treatment by alternative methods. Hypothetically, failure to clear misfolded and aggregated proteins (i.e., beta-amyloid) in AD brains and peripheral blood mononuclear cells (PBMCs) implicates BCG in upgrading the unfolded protein response (UPR). To test this hypothesis, pre- versus post-BCG PBMC proteins of the UPR pathway were compared in six NMIBC patients by capillary immunoelectrophoresis on an Abby instrument. PERK, the endoplasmic reticulum (ER) resident kinase, a stress-activated sensor, and its substrate alpha component of the eIF2 translation factor (eIF2a) complex inactivation were considered as potentially proapoptotic via a downstream proapoptotic transcription factor only if persistently high. GAPDH, a glycolytic marker of innate immunocyte training by BCG, and eight other UPR proteins were considered antiapoptotic. Summation of antiapoptotic %change scores per patient showed that the older the age, the lower the antiapoptotic %change. Higher antiapoptotic scores were observed upon a longer time from BCG treatment (with the exception of the patient in her ninth decade of life). Studies with more individuals could substantiate that BCG enhances the antiapoptotic aggregate-clearance effect of the UPR in PBMCs of NMIBC patients, which hypothetically protects brain cells against AD.